Imidazolium-based ionic liquids used as additives in the nanolubrication of silicon surfaces - Amorim, Patrícia M.; Ferraria, Ana M.; Colaço, Rogério; Branco, Luís C.; Saramago, Benilde (Beilstein Journal of Nanotechnology, 2017)
In recent years, with the development of micro/nanoelectromechanical systems (MEMS/NEMS), the demand for efficient lubricants of silicon surfaces intensified. Although the use of ionic liquids (ILs) as additives to base oils in the lubrication of steel/steel or other types of metal/ metal tribological pairs has been investigated, the number of studies involving Si is very low. In this work, we tested imidazolium-based ILs as additives to the base oil polyethylene glycol (PEG) to lubricate Si surfaces. The friction coefficients were measured in a nanotribometer. The viscosity of the PEG + IL mixtures as well as their contact angles on the Si surface were measured. The topography and chemical composition of the substrates surfaces were determined with atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS), respectively. Due to the hygroscopic properties of PEG, the first step was to assess the effect of the presence of water. Then, a series of ILs based on the cations 1-ethyl-3-methylimidazolium [EMIM], 1-butyl-3-methylimidazolium [BMIM], 1-ethyl-3-vinylimidazolium [EVIM], 1-(2-hydroxyethyl)-3-methylimidazolium [C2OHMIM] and 1-allyl-3-methylimidazolium [AMIM] combined with the anions dicyanamide [DCA], trifluoromethanesulfonate [TfO], and ethylsulfate [EtSO4] were added to dry PEG. All additives (2 wt %) led to a decrease in friction coefficient as well as an increase in viscosity (with the exception of [AMIM][TfO]) and improved the Si wettability. The additives based on the anion [EtSO4] exhibited the most promising tribological behavior, which was attributed to the strong interaction with the Si surface ensuring the formation of a stable surface layer, which hinders the contact between the sliding surfaces.
Keywords: additives; ionic liquids; lubricants; nanotribology; silicon